Uncoupling High Light Responses from Singlet Oxygen Retrograde Signaling and Spatial-Temporal Systemic Acquired Acclimation . Issue 3 (10th June 2016) - Carmody, Melanie; Crisp, Peter A.; d'Alessandro, Stefano; Ganguly, Diep; Gordon, Matthew; Havaux, Michel; Albrecht-Borth, Verónica; Pogson, Barry J.
Abstract : Uncoupling high light signal perception from distal signal reception shows that 1O2 EXECUTER-dependent retrograde signaling is required for initiation of systemic acquired acclimation in Arabidopsis. Abstract: Distinct ROS signaling pathways initiated by singlet oxygen ( 1 O2 ) or superoxide and hydrogen peroxide have been attributed to either cell death or acclimation, respectively. Recent studies have revealed that more complex antagonistic and synergistic relationships exist within and between these pathways. As specific chloroplastic ROS signals are difficult to study, rapid systemic signaling experiments using localized high light (HL) stress or ROS treatments were used in this study to uncouple signals required for direct HL and ROS perception and distal systemic acquired acclimation (SAA). A qPCR approach was chosen to determine local perception and distal signal reception. Analysis of a thylakoidal ascorbate peroxidase mutant ( tapx ), the 1 O2 -retrograde signaling double mutant ( ex1/ex2 ), and an apoplastic signaling double mutant ( rbohD/ F) revealed that tAPX and EXECUTER 1 are required for both HL and systemic acclimation stress perception. Apoplastic membrane-localized RBOHs were required for systemic spread of the signal but not for local signal induction in directly stressed tissues. Endogenous ROS treatments revealed a very strong systemic response induced by a localized 1 h induction of 1 O2 using the conditional flu mutant. A qPCR time course of 1 O2 induced systemic marker genes in directly and indirectly connected leaves revealed a direct vascular connection component of both immediate and longer term SAA signaling responses. These results reveal the importance of an EXECUTER-dependent 1 O2 retrograde signal for both local and long distance RBOH-dependent acclimation signaling that is distinct from other HL signaling pathways, and that direct vascular connections have a role in spatial-temporal SAA induction.